Microsoft Mathematics sebagai Media untuk Pengembangan Pembelajaran Matematika Siswa - Fara Syifa Nabila Siregar; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to find out how Microsoft Mathematics can serve as a supporting media in developing students' mathematics learning. The Systematic Literature Review (SLR) method was used in this study by reviewing various relevant scientific articles published between 2020 and 2025. The researcher took 10 main articles to be thoroughly analyzed. The selection of literature was done through several stages, namely identification, screening, feasibility test, and data synthesis, using predetermined inclusion and exclusion standards. The results of the analysis showed that the use of Microsoft Mathematics can improve understanding of mathematical concepts, problem-solving skills, and learning motivation. In addition, due to its interactive features, such as equation solver, scientific calculator, and 2D/3D graphs, this program is considered effective in visualizing abstract mathematical concepts.